An analysis on the implementation of the convention on the rights of the child in south american and european countries1 (2007)
The purpose of this paper is to analyze the recognized rights’ implementation made in the Convention on the Rights of the Child in South American and European countries. The empirical research used, as its mains source, data from the State Party Reports, write by governments and Alternative Reports write by non governmental organizations, which were sent to the “Committee on the rights of the child” –an organization created to monitor the implementation of the Convention–, in these countries. The following questions were examined: 1. Have the main rights of the Convention been effectively incorporated in the South American and European countries legislation? 2. What are the administrative measures adopted by these countries to monitor the implementation of the rights recognized by the Convention? 3. What are the social policies formulated by these countries to implement the children’s rights? 4. What are the roles of the non-governmental organizations on the child rights implementation process?